Dual-functional silver nanoparticle-enhanced ZnO nanorods for improved reactive oxygen species generation and cancer treatment - Yichao Tao; Wenbin Zhuang; Wensi Fan; Longxiang Zhou; Lihong Fan; Huanlong Qin; Yefei Zhu (iScience)
Summary: Recent advancements in sonodynamic therapy (SDT) for cancer treatment have highlighted the potential of enhancing reactive oxygen species (ROS) generation and improving therapeutic outcomes. This study introduces zinc oxide (ZnO) nanorods (NRs) in situ loaded with silver nanoparticles (ZnO@Ag NRs), designed to optimize ROS production under ultrasound irradiation and offer significant advantages in tumor specificity and biosafety. The transmission electron microscopy and elemental mapping confirmed the consistent size and monodispersed Ag nanoparticle for ZnO@Ag NR. Sonodynamic properties showed that ZnO@Ag NRs produce higher singlet oxygen and hydroxyl radicals under ultrasound. In vitro studies demonstrated excellent biocompatibility and enhanced cell-killing effects of ZnO@Ag NRs on CT-26 cells, while in vivo results confirmed its superior anti-tumor efficacy and biosafety. Furthermore, the ZnO@Ag NRs’ antibacterial properties were also confirmed, suggesting additional benefits in treating cancers associated with bacterial infections. Collectively, these findings establish ZnO@Ag NRs as a potent and safe agent for ultrasound-driven cancer therapy.